Management science, operations research and project management - Mateo, José Ramón San Cristóbal (Gower Publishing Limited Gower Publishing Compan, 2015)
Due to its societal and economic relevance, Project Management has become an important discipline and a concept critical to modern organizations, public and private. Operations Research gives the essential scientific contribution to the success of project management through the development of models and algorithms. This book deals with this topic